EFFECT OF HIGH-INTENSITY INTERVAL TRAINING ON FOOTBALL PLAYERS’ PERFORMANCE - Wang,Minjie (2023)
ABSTRACT Introduction High-intensity interval training contributes expressively to physical training and has been gradually applied to the soccer field. This sport has received more attention in colleges and universities in the country. However, studies are needed on the most appropriate training methods to improve the players’ ability among college students, increasing the competitive level among athletes. Objective Investigate the influence of high-intensity intermittent training on soccer players’ sports performance. Methods 30 student soccer players were selected at a university for six weeks, and four training sessions were held per week. The experimental group performed intermittent high-intensity training for training; the control group used the traditional aerobic resistance training method. For the experiment, indicator information was collected for integration and analysis before the start of activities and at the end of the six weeks. Results High-intensity intermittent training can improve the fitness index and FMS index of players and also can keep the fluctuation level in players’ performance higher; the range of performance improvement is considerably larger than the traditional aerobic training method. Conclusion High-intensity intermittent training can improve players’ fitness and agility, reduce sports injuries, improve physical reserve, and promote the progress of soccer players’ sports achievements. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.